FOOD SECURITY AND ITS PLACE IN THE STRUCTURE OF ECONOMIC SECURITY OF THE STATE (INNOVATIVE ECONOMY, 2022)
Zakhodym M.V. FOOD SECURITY AND ITS PLACE IN THE STRUCTURE OF ECONOMIC SECURITY OF THE STATEPurpose. The aim of the article is clarification of the essence of food security and determining its place in the structure of economic security of the state.Methodology of research. General scientific and special research methods were used in the process of research, namely: monographic – for theoretical generalization of the essence of food safety, analysis of research results of other scientists-researchers; economic and statistical – in the analysis of the level of consumption of the main types of food of the population of Ukraine, abstract and logical – to formulate conclusions.Findings. The essence of food security is highlighted. Its place in the structure of economic security of the state is established, considering that the last opens internal possibilities and defines strategic alternatives of social and economic growth for maintenance of public welfare. It is determined that the issue of providing the population with physiologically necessary food was and remains the most pressing problem of the state.It has been found that food security directly affects the health of a nation and, as a result, determines demographic security. The urgency of providing the population with high-quality food at the level of scientifically sound consumption norms in terms of effective demand and guaranteeing food security of the country has been confirmed.Originality. The own vision of the essence of the concept of “food security” is offered, which, unlike the existing ones, is considered as a state of the economy that will guarantee physical, economic and social accessibility, food safety and quality, stability of food security at the rational level under normal conditions, and in case of emergencies – at the minimum level, and will ensure food sovereignty.Practical value. The obtained results of the study are to develop recommendations on important areas of state support to ensure food security and a stable economic situation and can be used by the Departments of Economic Development of the regions.Key words: food security, economic security, food, consumption rate, policy.
Keywords: food security; economic security; food; consumption rate; policy